Development of rapid guidelines : 3. GINMcMaster Guideline Development Checklist extension for rapid recommendations (2018)
ABSTRACT: Background: Practice guidelines require a substantial investment of resources and time, often taking between 1 and 3 years from conceptualisation to publication. However, urgent situations require the development of recommendations in a shorter timeframe. In this third and final article in the series exploring challenges and solutions in developing rapid guidelines (RGs), we propose guiding principles for the development of RGs. Methods: We utilised the Guideline International Network-McMaster Guideline Development Checklist (GDC) as a starting point for elements to consider during RG development. We built on those elements using the findings from a systematic review of guideline manuals, a survey of international organisations conducting RGs, and interviews of guideline developers within WHO. We reviewed initial findings and developed an intermediate list of elements, as well as narrative guidance. We then invited experts to validate the intermediate list, reviewing for placement, brevity and redundancy. We used this iterative process and group consensus to determine the final elements for RG development guidance. Results: Our work identified 21 principles within the topics of the Guideline International Network-McMaster GDC to guide the planning and development of RGs. Principles fell within 15 of the 18 checklist topics, highlighting strategies to streamline and expedite the guideline development process. Conclusions: We defined principles to guide the development of RGs, while maintaining a standardised, rigorous and transparent process. These principles will serve as guidance for guideline developers responding to urgent situations such as public health urgencies. Integration of these principles within currently disseminated guideline development standards will facilitate the use of those tools in situations necessitating RG recommendations.